SOME VIEWS ON THE PERSONALITY OF ISFANDIYARKHAN - Bakhodir Aminov (Scholar Express Journals, 2023)
The personality of Isfandiyarkhan (Asfandiyarkhan) is given classifications and tariffs by different historians and different people, especially one of the people of that time Polyozhoji Yusupov. However, we cannot say that all of them are close or far from the truth. Nevertheless, some historical works and memoirs of historical figures are close to reality descriptions of the personality of Isfandiyarkhan
Keywords: Isfandiyarkhan; Asafandyarkhan